Ethics, knowledge and truth in sports research : an epistemology of sport - McFee, Graham (Ethics and sport., 2010)
Argues that sound high-level research into sport requires a sound rationale for one's methodological choices, and that such a rationale requires an understanding of the connection between the practicalities of researching sport and the philosophical assumptions which underpin them.